2012
DOI: 10.4103/0377-4929.101739
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease in fine needle aspiration smears: A clinico-cytologic study of 18 pediatric cases and correlation with 68 adult patients

Abstract: Besides observation and interpretation errors, a significant difference between the two groups in respect of some clinico-cytomorphological features could have influenced the routine cytodiagnosis leading to lower pickup rate of pediatric KFD cases as compared to adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In a study comparing clinical-cytological features in adults and children, children were significantly less likely to have high cellularity and Kikuchi histiocyte counts >5% than adults. [19] Our study also showed that the positive rate of EBV, one of the trigger factors of KFD, was higher in children, particularly among boys compared in adults. Although ANA positivity was higher in women than in men, ANA positivity was higher in boys than in girls.…”
Section: Discussionsupporting
confidence: 69%
“…In a study comparing clinical-cytological features in adults and children, children were significantly less likely to have high cellularity and Kikuchi histiocyte counts >5% than adults. [19] Our study also showed that the positive rate of EBV, one of the trigger factors of KFD, was higher in children, particularly among boys compared in adults. Although ANA positivity was higher in women than in men, ANA positivity was higher in boys than in girls.…”
Section: Discussionsupporting
confidence: 69%
“…However, the diagnostic accuracy of FNAC is not high for KFD. In previous studies, the initial diagnostic accuracies of FNAC in diagnosing KFD vary, ranging from 10% to 75% 7,9‐11,17 . Diagnosing KFD using FNAC is challenging because plasmacytoid monocytes are not identified confidently in the FNAC smears 9 and crescentic histiocytes can be observed in a wide variety of lymphadenopathy, such as tuberculosis lymphadenitis and non‐Hodgkin's lymphomas 10 .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 KFD is a type of cervical lymphadenitis that occurs rarely in children. 21 KFD is rarely reported in children and an misdiagnosed as reactive lymphoid hyperplasia or malignancy clinically and pathologically also. 1,4,22 Most of clinical diagnosis in our study was that of tuberculous lymphadenitis and reactive lymphoid hyperplasia.…”
Section: Discussionmentioning
confidence: 99%